2022
DOI: 10.18494/sam3555
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrical Properties of Mn-doped and Mn–Al co-doped ZnO Thin Films Annealed at Different Temperatures for Photosensor Applications

Abstract: Mn-doped and Mn-Al co-doped zinc oxide (ZnO) thin films were deposited on glass substrates by RF magnetron sputtering at room temperature. The X-ray diffraction results revealed that both films consisted of a single phase and had a wurtzite structure with a c-axis orientation. The electrical properties, transmittance characteristics, surface properties, and crystal structures of the films were investigated following annealing at temperatures ranging from 200 to 500 °C. The results showed that the as-deposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…(14) In the pursuit of higher optical transmittance and electrical performance, many recent studies have proposed the formation of a metal/oxide double-layer film structure comprising an oxide film and a metal film. (15)(16)(17)(18) Such double-layer films are configured to suppress the reflection of visible light by the metal layer and therefore have relatively high transmittance. (19) It has also been shown that a metal film of less than 15 nm thickness tends to form an island film, that a multilayer film formed with such a metal film and an oxide film can be annealed to inhibit the formation of the island structure by the metal film, and that the thermal diffusion during annealing enables strong bonding between the oxide film and the metal film, which contributes to increased conductivity and optical transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…(14) In the pursuit of higher optical transmittance and electrical performance, many recent studies have proposed the formation of a metal/oxide double-layer film structure comprising an oxide film and a metal film. (15)(16)(17)(18) Such double-layer films are configured to suppress the reflection of visible light by the metal layer and therefore have relatively high transmittance. (19) It has also been shown that a metal film of less than 15 nm thickness tends to form an island film, that a multilayer film formed with such a metal film and an oxide film can be annealed to inhibit the formation of the island structure by the metal film, and that the thermal diffusion during annealing enables strong bonding between the oxide film and the metal film, which contributes to increased conductivity and optical transmittance.…”
Section: Introductionmentioning
confidence: 99%